DFT study and quantitative detection by surface‐enhanced Raman scattering (SERS) of ethyl carbamate†. (7th October 2013) - Yang, Danting; Mircescu, Nicoleta E.; Zhou, Haibo; Leopold, Nicolae; Chiş, Vasile; Oltean, Mircea; Ying, Yibin; Haisch, Christoph
<x xml:space="preserve">Abstract</x> Ethyl carbamate (EC), a potentially toxic compound, is found in alcoholic beverages and fermented foodstuff. A combined experimental and theoretical study of Raman on EC is reported in this work for the first time. The Raman bands observed for EC in solid phase are characteristic for the carbonyl group, C―C, C―H and N―H stretching and deformation vibrations. These spectral features coupled with a pKa study allowed establishing the neutral species of EC present in the aqueous solutions experimentally tested at different concentrations. In addition, by performing a density functional theory study in the gas phase, the calculated geometry, the harmonic vibrational modes, and the Raman scattering activities of EC were found to be in good agreement with our experimental data and helped establish the surface‐enhanced Raman scattering (SERS) behavior and EC adsorption geometry on the silver surfaces. The Raman peak at 1006 cm−1, assigned to the υs(CC) + ω(CH) modes, the strongest and best reproducible peak in the SERS spectra, was used for a quantitative evaluation of EC. The limit of detection, which corresponds to a signal‐to‐noise ratio equal to 3, was found to be 2 × 10−7 M (17.8 µg l−1). SERS spectra obtained by using hydroxylamine hydrochloride‐reduced silver nanoparticles provide a fast and reproducible qualitative and quantitative determination of EC in aqueous solution. Copyright © 2013 John Wiley & Sons, Ltd.